Transformações microestruturais de silicatos em condições termodinâmicas extremas - Pinho, Lucas Max Estrela (Universidade Federal de São Carlos, 2025)
This study investigated the structural transformations of two silicate systems: lead metasilicate (PbSiO3 - PS) and lithium metasilicate (LiSiO3 - LS), under extreme thermodynamic conditions, with emphasis on the influence of high pressures and temperatures. Lead silicates stand out for their broad ability to form glasses and glass-ceramics with varied compositions, enabling applications ranging from domestic uses to advanced technologies. In these materials, crystallization control, through nucleation, growth, and phase stabilization, is essential for achieving specific properties. In this context, PbSiO3 emerges as an ideal model system, with distinct Raman signatures and a structure accessible via X-ray diffraction, allowing a precise assessment of the thermodynamic variables involved in the crystallization of glasses via heterogeneous nucleation. In situ analyses under high pressure were performed on three PS phases: one stable (monoclinic) and two metastable (hexagonal and low symmetry). The combination of Raman spectroscopy and synchrotron X-ray diffraction revealed a high structural sensitivity to hydrostatic compression, with indications of phase transitions starting at approximately 5 GPa and marked changes above 14 GPa. Properties such as compressibility, fundamentals for describing crystal evolution, were also determined. Additionally, lithium metasilicate (LiSiO3), a precursor for glass-ceramics, was studied using Raman spectroscopy as a function of temperature and time. Crystallization was found to be inducible both by thermal increase and by prolonged treatments at intermediate temperatures (around 500°C), highlighting the importance of kinetics in microstructural control. Progressive crystallization was evidenced by transformations in spectral bands, indicating nucleation and growth even below the critical temperature. The data obtained contributed to the understanding of the mechanisms of nucleation, growth, and structural reorganization in silicates, demonstrating that pressure, temperature, and time are key variables in inducing and controlling glass-to-crystal transitions. The results reinforce the importance of in situ and multidisciplinary experimental approaches for the development of glass-ceramic materials with tunable properties.
Microstructural transformations of silicates under extreme thermodynamic conditions
Keywords: Silicatos; Espectroscopia Raman; Alta pressão; Alta temperatura; Cristalização; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTRUTURA DE LIQUIDOS E SOLIDOS; CRISTALOGRAFIA; 9. Indústria, Inovação e Infraestrutura